Gross worker flows in the presence of informal labor markets: evidence from Mexico, 1987 - 2002 - Mariano Bosch; William F. Maloney (Institute for the Study of Labor (IZA), 2007)
This paper applies recent advances in the study of labor market dynamics to a representative developing country with a large unregulated of informal sector. It confirms the relevance of the recent mainstream models and debates surrounding gross worker flows to the developing country context, and offers a new view of the role of the informal sector and its role in labor market adjustments. It finds, first, that the formal salaried sector shows the same procyclical job finding rate and mildly countercyclical separation behavior identified in the recent US literature by Shimer (2005a) and Hall (2005). The unregulated informal sector, however, shows reasonable acyclicality in the job finding rate coupled with sharp countercyclical movements in the job separation rate, consistent with standard small firm dynamics and Davis and Haltiwanger (1992 and 1999). The differential behavior of regulated and unregulated sectors, and the finding of relative wage rigidity in the former, sheds suggestive light on the debate surrounding countercyclical job finding behavior in the US. Second, the patterns of worker transitions between all sectors, formal and informal correspond to the job-to-job dynamics observed in the US and not to the traditional idea of informality constituting the inferior sector of a segmented market. That said, the counter cyclical job finding in the formal sector combined with the acyclical job finding in informality does lead to the latter absorbing relatively more labor during downturns, even as its increased separation rates drive movements in unemployment.
Keywords: 330; Arbeitsmarkt; Informeller Sektor; Mexiko